Tailoring the Reversible Phase Transition of Perovskite Nanofiber Electrodes for High-Performance and Durable Reversible Solid Oxide Cells - Yin, Chaofan; Yang, Jiaming; Feng, Jiangyuan; Sun, Yueyue; Liu, Zhengrong; Wang, Junkai; Cui, Jiajia; Xue, Zixuan; Zhang, Liang; Zhou, Yucun; Zhou, Jun; Xu, Liangfei; et al. (Nano-Micro Letters, 2025)
Reversible solid oxide cells (RSOCs) are capable of converting various energy resources, between electricity and chemical fuels, with high efficiency and flexibility, making them suitable for grid balancing and renewable energy consumption. However, the practical application of RSOCs is still limited by the insufficient activity and stability of the electrodes in different operating modes. Herein, a highly efficient symmetrical electrode composed of La0.3Sr0.6Ti0.1Co0.2Fe0.7O3−δ (LSTCF) nanofibers and in situ exsolved Co3Fe7 nanoparticles is developed for boosting the performance of RSOCs. The reversible phase transition, high activity and stability of the electrode have been confirmed by a combination of experimental (e.g., transmission electron microscopy and X-ray absorption fine structure) and computational studies. Electrolyte-supported RSOCs with the symmetrical electrode demonstrate excellent catalytic activity and stability, achieving a high peak power density of 0.98 W cm−2 in the fuel cell mode using H2 as the fuel (or 0.53 W cm−2 using CH4 as the fuel) and a high current density of 1.09 A cm−2 at 1.4 V in the CO2 electrolysis mode (or 1.03 A cm−2 at 1.3 V for H2O electrolysis) at 800 °C while maintaining excellent durability for over 100 h. Highlights: 1 La0.3Sr0.6Ti0.1Co0.2Fe0.7O3−δ (LSTCF) nanofibers showed high structural reversibility. 2 LSTCF fibers and CoFe nanoparticles were reconstructed through a reversible phase transition process. 3 The LSTCF fiber electrode demonstrated excellent activity and stability for power and fuel co-generation.